1972
DOI: 10.1515/zna-1972-0415
|View full text |Cite
|
Sign up to set email alerts
|

Photolyse des Äthylens im Bereich 147 — 193 nm / Ethylene Photolysis At 147 — 193

Abstract: Ethylene photolysis was investigated at 147, 163, 185 and 193 nm. The following three primary processes were observed at all wavelengthsCCC(1) was independent of all experimental parameters tested: temperature, pressure, wavelength, scavenger, and light intensity. (2) decreases with increasing pressure and increases with increasing photon energy. (3) shows almost no pressure dependence at 185 nm and decreases in importance with increasing photon energy. A kinetic analysis shows that participation of at least t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
2

Year Published

1972
1972
1988
1988

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 0 publications
2
21
2
Order By: Relevance
“…This intensity was much lower than used in previous studies; in particular in the study by Potzinger et al the absorbed intensity was 1.7 x 1017 quanta 1-' s-' (13). The lower light intensity caused two differences between the mechanism outlined here and that proposed in the latter study.…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…This intensity was much lower than used in previous studies; in particular in the study by Potzinger et al the absorbed intensity was 1.7 x 1017 quanta 1-' s-' (13). The lower light intensity caused two differences between the mechanism outlined here and that proposed in the latter study.…”
Section: Resultscontrasting
confidence: 55%
“…The photolysis of ethylene at 185 nm has been shown to involve three primary processes and it has been suggested that at least three excited states of ethylene contribute to these reactions (13). Deactivation without decomposition is also important at 185 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At lower photon energies (5.6-6.2 e V) there IS barely enough energy for the occurrence of the overall process ! !.H=5_5eV (8) and the high relative yield of C2H2 can definitely be ascribed to the elimination of DCl from a single carbon atom:…”
Section: (4)mentioning
confidence: 97%
“…The quantum yields of the other products were determined by using ethylene (1.5 torr) as a chemical actinometer. The quantum yield of acetylene at 147 and 123.6 nm was established [7][8] to be 1 ± 0.05. At 104.8-106.7, <1>(C 2H2) has been estimated [9] to be 0.75 ± 0.05.…”
mentioning
confidence: 99%